A Systematic Review of Patient Heart Failure Self-care Strategies. Issue 2 (March 2015) - Harkness, Karen; Spaling, Melisa A.; Currie, Kay; Strachan, Patricia H.; Clark, Alexander M.
Abstract : Background: Self-care is at the foundation for living with a chronic condition such as heart failure (HF). Patients with HF express difficulty with translating self-care knowledge into understanding "how" to engage in these activities and behaviors. Understanding the strategies that patients develop to engage in self-care will help healthcare providers (HCPs) improve support for unmet self-care needs of HF patients. The purpose of this systematic review was to highlight strategies that HF patients use to accommodate self-care recommendations into the reality of their daily lives. Methods: A systematic review using qualitative meta-synthesis was carried out. Included studies had to contain a qualitative component and data pertaining to self-care of HF from adults older than 18 years and be published as full papers/theses beginning 1995. Ten databases were searched until March 19, 2012. Results: Of 1421 papers identified by the search, 47 were included. Studies involved the following: 1377 patients, 45% women, mean age of 67 years (range, 25–98 years), 145 caregivers, and 15 HCPs. Approaches to self-care reflected both perception- and action-based strategies and were a means to effectively manage HF. Although HF patients often expressed difficulty on how to integrate self-care recommendations into their daily lives, they developed intentional, planned strategies that harnessed previous experiences. Conclusions: Healthcare providers must appreciate that patients view self-care as an "adaptation" that they undertake to maintain their independence and quality of life. In addition, HCPs must recognize that because self-care is a process of learning over time from experience, an individualized approach that emphasizes how to self-care must be adopted for patients to develop the necessary HF self-care skills.